2014
DOI: 10.1021/jm500432n
|View full text |Cite
|
Sign up to set email alerts
|

Novel N-Linked Aminopiperidine-Based Gyrase Inhibitors with Improved hERG and in Vivo Efficacy against Mycobacterium tuberculosis

Abstract: DNA gyrase is a clinically validated target for developing drugs against Mycobacterium tuberculosis (Mtb). Despite the promise of fluoroquinolones (FQs) as anti-tuberculosis drugs, the prevalence of pre-existing resistance to FQs is likely to restrict their clinical value. We describe a novel class of N-linked aminopiperidinyl alkyl quinolones and naphthyridones that kills Mtb by inhibiting the DNA gyrase activity. The mechanism of inhibition of DNA gyrase was distinct from the fluoroquinolones, as shown by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
41
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 27 publications
1
41
0
Order By: Relevance
“…During the preparation of the manuscript, a closely related class of N-linked aminopiperidinyl-based gyrase inhibitors was described by AstraZeneca (16). M. tuberculosis DNA gyrase supercoiling and the cleavage complex assays confirmed their mode of action.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the preparation of the manuscript, a closely related class of N-linked aminopiperidinyl-based gyrase inhibitors was described by AstraZeneca (16). M. tuberculosis DNA gyrase supercoiling and the cleavage complex assays confirmed their mode of action.…”
Section: Discussionmentioning
confidence: 99%
“…This exercise resulted in the identification of novel M. tuberculosis DNA gyrase inhibitors (MGIs), a new family of promising compounds with potential for the treatment of TB disease already reported in the literature as antimycobacterial and antibacterial agents (12,13,14,15). Recently, AstraZeneca has reported anti-TB activity for NBTIs (16).…”
mentioning
confidence: 99%
“…This data suggests that R 1 substituents at the C-7 position of the LHS ring is amenable for chemical diversity Fluoro substituted aminopiperidine based NBTIs have shown good oral bioavailability and hERG selectivity as compared to their nonfluoro counterparts. 8,9 In order to identify compounds with good oral pharmacokinetic properties, we introduced a fluoro substitution in the linker portion of compounds 10 and 11 to result in compounds 18 and 19, respectively. This The scatter plot presented in Figure 3 for hERG IC 50 suggested that calculated lipophilicity (AZ logD) of <1.5 is ideal for achieving good hERG selectivity for compounds with bulky substitutions at R 1 position of LHS ring (green encircled in Figure 3).…”
Section: As Shown Inmentioning
confidence: 99%
“…[8][9][10]16 The synthesis of compounds with bulky substitutions (2−9) are illustrated in Scheme 1. Nucleophilic displacement of halo substituted naphthyridones (I) with corresponding carbinol (II) using cesium carbonate under thermal heating condition resulted in title compounds 2−19.…”
mentioning
confidence: 99%
See 1 more Smart Citation